2005
DOI: 10.3732/ajb.92.4.736
|View full text |Cite
|
Sign up to set email alerts
|

Floral phenology and compatibility of sawgrass, Cladium jamaicense (Cyperaceae)

Abstract: Sawgrass, Cladium jamaicense, is the dominant macrophyte in the Florida Everglades. We examined sawgrass flowering phenology and compatibility reactions in ex situ and in situ populations over 2 yr. Sawgrass flowers in May in southern Florida. Flower maturation was relatively synchronous within an inflorescence. Along the entire inflorescence, functionally male flowers emerged initially, followed by stigmas, then anthers of hermaphroditic flowers. Flowers of each sex expanded over 2 d with less than 1 d in bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…In an evolutionary sense, however, plants can affect the direction and distance of dispersed seeds, and even their specific deposition site (18,19). For example, some wind-dispersed species release seeds during turbulent winds (14,20,21), when they are more likely to ride updrafts and reach distant sites (14). Some terrestrial plant seeds also have adaptations to facilitate movement along the ground and settlement in crevices (14).…”
Section: Discussionmentioning
confidence: 99%
“…In an evolutionary sense, however, plants can affect the direction and distance of dispersed seeds, and even their specific deposition site (18,19). For example, some wind-dispersed species release seeds during turbulent winds (14,20,21), when they are more likely to ride updrafts and reach distant sites (14). Some terrestrial plant seeds also have adaptations to facilitate movement along the ground and settlement in crevices (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis for the southern section suggests fragmentation via a loss of cohesion of sawgrass ridges and consolidation of sloughs, but not a total disappearance of sawgrass. The sympodial growth form of sawgrass allows it to persist in less than ideal conditions for an extended period (Snyder and Richards 2005) by growing up, forming tussocks-or fragmenting at a local scale-instead of growing in continuous strands. This appears to be the pattern reflected in the southern portion of WCA3AS.…”
Section: Landscape Analysismentioning
confidence: 99%
“…Daehler and Strong (1994) suggested that inbreeding depression was a possible factor contributing to the large variability of reproductive output in a study of clones of Spartina alterniflora. Snyder and Richards (2005) also noted that sawgrass can self-fertilize, although the sexes within an inflorescence are usually temporally separated. Ivey and Richards (2001) have found a rather uniform genetic structure in sawgrass throughout the Everglades water conservation areas.…”
Section: Discussionmentioning
confidence: 99%
“…Both crossing and selfing may occur in sawgrass populations in response to such factors as clone size, number of ramets, and timing of flowering (Snyder and Richards 2005). Variations in seed mass for selfed and out-crossed seeds of sawgrass are unknown for sawgrass, but seed mass of selfed seed is known to be smaller in some native species (Pinto-Torres and Koptur 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation